Fixing One's History: George S. Patton's Changes in his Personal Diary. (January 2021) - Feldmann, Daniel
George S. Patton is a well-known American Army commander of the Second World War. The personal diary he kept from 1942 to 1945 is a must-read source to understand the history and the performance of the US Army in the war. However, the conflicting versions of this diary and the many after-the-fact additions can lead to significant misinterpretations of Patton's performance. This article examines the editorial evolutions of the diary, details what were the most significant modifications, and shows how they distorted what Patton thought of fellow officers as well as his role in the Normandy campaign and the Battle of the Bulge.